Vitamin D assessment in patients with benign paroxysmal positional vertigo - Mohamed M Elmoursy Kasem (Wolters Kluwer Medknow Publications, 2021)
Background Benign paroxysmal positional vertigo (BPPV) is the most common type of peripheral vestibular disorder. Several studies have correlated between vitamin D deficiency and the development of BPPV. Objectives The aim of the study was to measure the serum levels of vitamin D and serum calcium in patients with BPPV and if vitamin D deficiencies have a role in the development of BPPV. Patients and methods The study included 50 patients with first attack of BPPV based on characteristic nystagmus on Dix-Hallpike's and Supine-Roll's tests, where serum levels of 25-hydroxyvitamin D and calcium, including both total and ionized forms, were measured and compared with control group of 25 apparently healthy individual. Results The mean vitamin D level in patients with BPPV and control groups was 22.80±11.26 and 29.30±10.62 ng/ml, respectively. There was a statistically significant difference regarding vitamin D levels in BPPV group in comparison with the control group (P=0.019). Moreover, there was a statistically significant difference regarding vitamin D deficiency in patients with BPPV in comparison with the control group (P=0.046). Conclusion Vitamin D deficiency contributes to the development of BPPV through abnormal calcium metabolism in the inner ear.